Analisis bibliometrik artificial intelligence pada database crossref (2014 – 2024) - Dovel Pirmanto (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2025)
Background of the Study: Artificial Intelligence (AI) technology is experiencing very rapid development and has an impact on various sectors of human life. Objectives: This study aims to analyze articles from various publications indexed by the crossref database in 2014 - 2024. Data analysis includes publication of articles from year to year, types of publication documents, Artificial Intelligence keyword mapping. Method: The method applied in this study is an evaluative and descriptive quantitative method with bibliometric analysis in studying and analyzing research patterns and trends. The results of the analysis of publication data for the last 11 years on Artificial Intelligence have increased from year to year, but decreased in 2017. Finding: The results of the study through bibliometric analysis show that out of 1000 publications that discuss Artificial Intelligence, they come from articles with a percentage of 55.2%. The keywords often studied are the relationship between Artificial Intelligence and systems, technology, impact, human rights, applications, education, development and challenges. Conclusion: Research is scattered or AI research trends in 2024 such as the relationship between Artificial Intelligence and attacks, acceptance, voice, digital transformation, biotechnology and digital technology.